The Covid-19 pandemic and the increase in alcohol consumption in Brazil (Research, Society and Development, 2021)
In view of the recent discussion about the Covid-19 pandemic and the adoption of measures of social distancing in Brazil, this article presents the possible causes of the increase in alcohol consumption as a consequence of the effects of the pandemic. There are still debates on how distancing strategies were adopted to contain the spread of the virus and directly affected people's lives through extreme decision-making, such as social isolation, including banning the operation of establishments, and, consequently, consumption of alcohol, which was carried out in these spaces, started to be done more frequently at home. Furthermore, in view of this problem, the article in question has the general objective of investigating, through the structuring of a narrative literature review, the influence of the pandemic and isolation measures on the increase in alcohol consumption. The methodology of this study was carried out through the deductive method through the collection of bibliographic data of a qualitative and documentary nature, forming an exploratory research. Thus, as the research performed, a peak in the consumption of alcoholic beverages during the period of social isolation was found, mainly by the young public. In this context, it should be emphasized that early intervention in cases of alcohol dependence is extremely important in preventing the development of chronic alcoholism in order to establish better public health strategies and measures.